PENGUKURAN KINERJA MENGGUNAKAN METODE VALUE FOR MONEY PADA PEMERINTAHAN KABUPATEN REMBANG PERIODE 2020-2022 - Mukhoddasah, Siti Nahrul; Afandi, Johan (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
This research aims to be a source of knowledge regarding the economic level, efficiency and effectiveness of the Rembang Regency Government Budget Realization Report. The type of research used in this research is descriptive quantitative. The population in this research is all budget realization report data using the sampling method, namely the purposive sampling method. Researchers chose to use secondary data with documentation and observation data collection techniques. The data that has been collected is then calculated using the value for money method and then conclusions are drawn. The research results show that in terms of economic ratios, Rembang district is said to be economical because in the last 3 years it has been at a percentage of 90%-100%. In terms of efficiency ratios, the Rembang district government has experienced a drastic decline over the last 3 years, with an average of 93.09% falling under the criteria of being less efficient. In terms of effectiveness ratio, the Rembang district government has experienced ups and downs in percentage over the last 3 years, but it is not bad because the average is 99.9%. Viewed from an economic perspective from an Islamic perspective, the Rembang Regency Government carries out its financial performance economically, by not committing wasraf/waste. In terms of efficiency from an Islamic perspective, it is still not good, because lack of efficiency is considered a violation of the mandate carried out. In terms of effectiveness, it is in accordance with an Islamic perspective, according to a hadith from Muslim history which describes the importance of choosing good and responsible leaders in government.